Sharia Economic Empowerment Efforts Through Koperasi Wanita Srikandi, Kelurahan Sidokerto, Kecamatan Buduran, Sidoarjo - Hersa, Hersa Farida Qoriani (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2020)
The purpose of this research is to analyze the role of Koperasi wanita in efforts to empower women and empower the Islamic economy (especially mothers around the Koperasi wanita, Sidokerto, Kecamatan Buduran, Sidoarjo), the welfare conditions of members of koperasi Wanita, and the potential of Koperasi Wanita the future. The study was conducted at the Koperasi Wanita